Working towards health equity for ethnic minority elders: spanning the boundaries of neighbourhood governance. Issue 2 (23rd December 2020) - Carlsson, Hanna; Pijpers, Roos
Abstract : Purpose: This paper analyses how neighbourhood governance of social care affects the scope for frontline workers to address health inequities of older ethnic minorities. We critically discuss how an area-based, generic approach to service provision limits and enables frontline workers' efforts to reach out to ethnic minority elders, using a relational approach to place. This approach emphasises social and cultural distances to social care and understands efforts to bridge these distances as "relational work". Design/methodology/approach: The authors conducted a two-year multiple case study of the cities of Nijmegen and The Hague, the Netherlands, following the development of policies and practices relevant to ethnic minority elders. They conducted 44 semi-structured interviews with managers, policy officers and frontline workers as well as 295 h of participant observation at network events and meeting activities. Findings: Relational work was open-ended and consisted of a continuous reorientation of goals and means. In some cases, frontline workers spanned neighbourhood boundaries to connect with professional networks, key figures and places meaningful to ethnic minority elders. While neighbourhood governance is attuned to equality, relational work practice fosters possibilities for achieving equity. Research limitations/implications: Further research on achieving equity in relational work practice and more explicit policy support of relational work is needed. Originality/value: The paper contributes empirical knowledge about how neighbourhood governance of social care affects ethnic minority elders. It translates a relational view of place into a "situational" social justice approach.